Performance analysis for a 2 (3HSS+S) parallel manipulator with double moving platforms. (2nd September 2016) - Cheng, Gang; Zhao, Zunzhong; Shan, Xianlei
The working efficiency of a parallel manipulator with double moving platforms is better than a parallel manipulator with a single moving platform. In this study, a 2 (3HSS+S) parallel manipulator is presented, and the topology model of the parallel manipulator is established. After calculating, the position and velocity of the manipulator were analysed, and the workspace was obtained under the constraint conditions of parallel manipulator. Within the workspace, the motion dexterity was studied using the reciprocal of the condition number of the motion Jacobian matrix. The static load-bearing performance was analysed through the two norms of the force Jacobian matrix. The two performance indices, which are motion dexterity and static load bearing, indicate that the manipulator has favourable performance characteristics in the range of positive values of angle, which is the rotation in z-axis, but it has a singular position in the range of large negative values of angle. Within the scope of the singular point, the maximum and minimum eigenvalues of the stiffness matrix and the kinematic stiffness index (KSI) were analysed. It has been concluded that the stiffness characteristics are poor near the singular points, and the correctness analysis of the two performance indices has been verified by the results.